A study of wrecked Dovekies (Alle alle) in the western North Atlantic highlights the importance of using standardized methods to quantify plastic ingestion. Issue 1 (15th December 2016) - Avery-Gomm, Stephanie; Valliant, Michelle; Schacter, Carley R.; Robbins, Katherine F.; Liboiron, Max; Daoust, Pierre-Yves; Rios, Lorena M.; Jones, Ian L.
Abstract: Quantification of plastic ingestion across a range of seabirds is required to assess the prevalence of plastics in marine food webs. We quantified plastic ingestion in beached Dovekies ( Alle alle ), following a wreck in Newfoundland, Canada. Of 171 birds, 30.4% had ingested plastic (mean 0.81 ± 0.30 SE pieces per bird, mass 0.005 ± 0.002 SE g per bird). Most plastics were fragments of polyethylene and polypropylene. Surprisingly, 37% were burned or melted, indicating a previously unreported source of ingested plastics (incinerated waste). We found no relationship between plastic ingestion and age, sex or body condition. By comparing our results with a similar nearby study, we illustrate the need for researchers to adopt standardized methods for plastic ingestion studies. We underline the importance of using histological techniques to reliably identify gastric pathologies, and advise caution when inferring population level trends in plastic ingestion from studies of emaciated, wrecked birds. Graphical abstract: In contrast to other studies in Newfoundland, in the western North Atlantic, 30% of beach-cast Dovekies ingested plastics – highlighting the need for researchers to use standardized methods for quantifying plastic ingestion. Illustration by Adam D. P. Cross. Highlights: 30.4% of emaciated beach-cast Dovekies (N = 171) from NW Atlantic ingested plastic. Incinerated garbage a source of seabird-ingested plastic in Newfoundland, Canada Histology is required to accurately identify lesions such as ulcers. No link between cause of death (starvation) and the ingested plastic was found. Standardized methods required to facilitate comparisons between ingestion studies.